2001
DOI: 10.1023/a:1019565229886
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The treatment of urinary incontinence represents an important medico-social problem, notwithstanding the offered 90 products of treatment. The authors summarice their experience on the treatment of urinary incontinence with clenbuterol for the period 1988-1997. During this period total of 335 patients (163 women and 72 men), aged between 30 and 73 were treated. The medicine was used in the treatment of women with stress incontinence (60) and urge incontinence (103). In cases of combination between urinary inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Moreover, ␤ 2 -adrenergic receptor agonists also relax the detrusor muscle during bladder filling (57,59). In a randomized controlled trial, clenbuterol induced significant clinical improvement and normalized the main urodynamic indicators of SUI in both men and women in the presence of normal sphincter activity (65). In addition, a limited open-label trial reported a similar rate of improvement in men with mild to moderate SUI after prostatectomy (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ␤ 2 -adrenergic receptor agonists also relax the detrusor muscle during bladder filling (57,59). In a randomized controlled trial, clenbuterol induced significant clinical improvement and normalized the main urodynamic indicators of SUI in both men and women in the presence of normal sphincter activity (65). In addition, a limited open-label trial reported a similar rate of improvement in men with mild to moderate SUI after prostatectomy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have shown that clenbuterol could relieve symptoms of stress and urge incontinence (41, 65), we did not observe a therapeutic potential of clenbuterol in either urethral function or morphology. Previous clinical trials administered clenbuterol with a dose at 10 -20 g two or three times daily for 2-4 wk to enrolled subjects (22,28,30,58,62,65). The dose used in this experiment was higher than the clinical dose and may suggest that rats are less sensitive to this ␤ 2 -adrenoceptor agonist.…”
Section: F442mentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, to treat overactive bladder in MG, serotonergic drugs (e.g., serotonin-noradrenaline reuptake inhibitors) [ 13 ] and selective adrenergic beta 3 receptor agonists [ 20 ] may be the best options. When stress urinary incontinence is proved by examination and tests, clenbuterol (an adrenergic beta 2 receptor agonist) [ 21 ] and mesh surgeries for counteracting pelvic floor descent are good choices. Again, urodynamics has a place, but clinical examination is still important to perform in all MG patients.…”
Section: Discussionmentioning
confidence: 99%